State banking in early America : a new economic history - Bodenhorn, Howard (Oxford University Press, 2003)
During the latter half of the 20th century such features of early American financial markets as free banking, branch banking, deposit insurance, and micro-banking were radically reinterpreted. This text synthesizes extant research and finds alternative interpretations.